2022
DOI: 10.1021/acs.jchemed.2c00524
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Bioenergy Transformation: The Discharge/Charge Reaction of Vitamin B2 in Lithium-Ion Batteries

Abstract: Organic electrode materials are progressively becoming a research hotspot for energy storage materials due to their renewable and environmentally friendly features. Inspired by the energy transduction mechanism of flavin adenine dinucleotide (FAD) on the inner mitochondrial membrane of living organisms, the lithium storage electrochemical behavior of riboflavin (RF, vitamin B2) in lithium-ion batteries (LIBs) has been explored. The students are encouraged to find inspiration from organisms to design energy sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, riboflavin (vitamin B2) acts as an electroactive precursor for the biochemical synthesis of nucleotides. However, only a few studies have shown the potential of these molecules for electrochemical energy storage devices [ 29 ], adsorbed on the surface of materials such as graphite or singled-wall carbon nanotubes (SWCNT), or for lithium-ion batteries [ 30 ]. In addition, they have been used to enhance the oxygen evolution reaction (OER) combined with Ni-MOF [ 31 ] or in an organic flow desalination battery [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, riboflavin (vitamin B2) acts as an electroactive precursor for the biochemical synthesis of nucleotides. However, only a few studies have shown the potential of these molecules for electrochemical energy storage devices [ 29 ], adsorbed on the surface of materials such as graphite or singled-wall carbon nanotubes (SWCNT), or for lithium-ion batteries [ 30 ]. In addition, they have been used to enhance the oxygen evolution reaction (OER) combined with Ni-MOF [ 31 ] or in an organic flow desalination battery [ 32 ].…”
Section: Introductionmentioning
confidence: 99%